PROFIL PENYIMPANAN OBAT Profile penyimpanan obat di Puskesmas wosu Kabupaten Morowali - David, Moh; Nurlina, Nurlina; Zulkarnain, Iskandar (Makassar Pharmaceutical Science Journal (MPSJ), 2024)
Drug storage profiles are an importand factor ini drug management at community health center, because with proper storage of medicines it will be easier and more effective to guarantee the quality of medicines. This research aims to determine the procedures for regulating drugs and improving the quality of drug storage at the wosu healty center, bungku barat sub-district, morowali district. Data collection was carried out through interviews and using observation sheets regarding aspects of drug storage in community health centers including general aspects, special aspectsinclude requirements for drug storage warehouses with 15 aspects assesed with a persentage of 100%, special aspects include requirements of drug preparation with 5 aspects assessed with a percentage of 100% and document review includes procedures for recording drugs. From the result of research in the field there are still several problems that do not meet standards. How ever in general the results of this study show that drug storage, preparation of drugs, and recording of drugs at the wosu comunity health center, bungku barat sub- district, morowali regency are in the good category.